The Role Of Digital Transformation In Enhancing Operational Eficiency And Competitive Advantage In Manufacturing Industries - Prananta, Arie (Journal Management & Economics Review (JUMPER), 2025)
This study examines the role of digital transformation in enhancing operational efficiency and competitive advantage within manufacturing industries. Drawing on the Resource-Based View (RBV) and Port er’s competitive strategy framework, the research investigates both the direct and indirect effects of digital transformation, with operational efficiency serving as a mediating variable. Using a quantitative approach, data were collected from managerial-level respondents in manufacturing firms that had implemented digital initiatives within the past three years. The measurement and structural models were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results reveal that digital transformation significantly improves operational efficiency (β = 0.682, p < 0.001) and directly contributes to competitive advantage (β = 0.325, p < 0.001). Operational efficiency also has a strong positive impact on competitive advantage (β = 0.521, p < 0.001), confirming its mediating role. The findings highlight that efficiency gains are a key mechanism through which digital transformation delivers strategic benefits, while also generating direct competitive advantages through innovation, agility, and customer engagement. This study offers both theoretical contributions to the digital transformation literature and practical guidance for manufacturing firms and policymakers seeking to maximize the returns on digital investments.